PENGARUH PENANGANAN SPUTUM TERHADAP KUALITAS SPUTUM PENDERITA TBC SECARA MIKROSKPIS BAKTERI TAHAN ASAM - Teguh Budiharjo; Kuntjoro Adi Purjanto (Jurnal Riset Kesehatan, 2016)
Purpose of the study was to determine differences in the results of the microscopic examination of sputum BTA that is directly checked by way of delay 24 hours at room temperature. Type of research is descriptive analytical. Data analysis was using different testing Wilcoxon Dependent Test with 95% confidence level (alpha less than 0,05) and supported SPSS 21. There are 3 samples with 1+ results of 25 sputum samples were directly examined there are 8 samples with 2+ results, 14 samples with 3+ results. Where as for the examination of samples that postponed for 24 hours at a temperature of 25oC obtained 1+ results for 7 samples, 2+ with 6 samples, and 3+ of 12 samples are positive BTA. At 25 sputums samples were directly examined with delay methods for 24 hours at 25oC, obtained 6 sputum are more likely to be negative. There is no positive results and the same number will be checked with the methods of sputum delay for 24 hours at room temperature less than 19 sputums. This indicates that the examination of sputum delay for 24 hours at room temperature could lead to false negative results or even a false positive. There was the difference of the results between sputum directly examined by with be delayed 24 hours at room temperature 25oC .It is recomended that examination sputum TBC should be done soon to avoid a positive result or negative specious the results of investigation microscopic .